2016
DOI: 10.1253/circj.cj-15-0718
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glucagon-Like Peptide-1 and Tissue Characteristics of Coronary Plaque in Non-Diabetic Acute Coronary Syndrome Patients

Abstract: Low plasma GLP-1 during 75-g OGTT is associated with increased lipid content in non-diabetic patients with ACS, suggesting that plaque vulnerability is increased in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…AUC-GLP-1 values in the subjects in the present study ranged widely as in earlier studies 11 , 25 . Since there are no established data for a normal range of AUC-GLP-1 value during the OGTT, the extent of change in GLP-1 secretory capacity is difficult to determine by use of OGTT data.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…AUC-GLP-1 values in the subjects in the present study ranged widely as in earlier studies 11 , 25 . Since there are no established data for a normal range of AUC-GLP-1 value during the OGTT, the extent of change in GLP-1 secretory capacity is difficult to determine by use of OGTT data.…”
Section: Discussionsupporting
confidence: 79%
“…They conducted the OGTT by using almost the same blood sampling protocol as that used in our study, and AUC-GLP-1 in the normal control group was 969 ± 34 (mean ± SD, pmol/l ⨯ min). Mitsuhashi et al 25 reported data for AUC-GLP-1 tertiles in non-diabetic patients with acute coronary syndrome (n = 84): AUC < 395 (290 ± 84), AUC 395–660 (493 ± 73), and AUC > 660 (1,668 ± 1,229). In their study, the group with AUC < 395 had more lipid-rich coronary plaque than that in the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies have also shown the anti-fibrotic effects of GLP-1RAs. Reduced GLP-1 levels in plasma have been associated with atheroma instability and cardiac fibrosis in non-diabetic patients with ACS [ 188 ]. Initiating GLP-1RAs therapy shortly after a first AMI in patients with diabetes has been linked to a reduced risk of significant CV events [ 189 ].…”
Section: Novel Drugs and Their Anti-fibrotic Rolementioning
confidence: 99%